Controlling electron localization in H-2(+) by intense plasmon-enhanced laser fields - (:unkn) unknown (AMER PHYSICAL SOC, 2016)
We present a theoretical study of the H-2(+) molecular ion wave-packet dynamics in plasmon-enhanced laser fields. These fields may be produced, for instance, when metallic nanostructures are illuminated by a laser pulse of moderated intensity. Their main property is that they vary in space on a nanometric scale. We demonstrate that the spatial inhomogeneous character of the plasmonic fields leads to an enhancement of electron localization (EL), an instrumental phenomenon to control molecular fragmentation. We suggest that the charge imbalance induced by the surface-plasmon resonance near the metallic nanostructure is the origin of the increase in the EL.
Keywords: HIGH-HARMONIC-GENERATION; EMISSION; ATOMS